ANALYSIS OF FACTORS OF LEARNING DIFFICULTY FOR STUDENTS OF CLASS VII IN SOCIAL STUDIES SUBJECTS AT SMP DARUL KIROM - Nadia Ila Sabila; Chientya Annisa Rahman Putrie (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
This research aims to determine the factors causing students learning difficulties of social science subjects at SMP Darul Kirom Bekasi. The research method used is a quantitative with technique of data collection used is questionnaire. The sample in this research is 57 students from all VII grade at SMP Darul Kirom with the sampling technique using simple random sampling. The results showed that were 8 factors that formed from the learning difficulties for class VII students at SMP Darul Kirom.. The factors that have been formed consist of: motivational factor with the highest eigenvalue of 4,879, school factor with eigenvalue of 2,496, attitude factor with eigenvalue of 2,325, psychological factor with eigenvalue of 1,871, interest factor with eigenvalue of 1,619, parental support factor with eigenvalue of 1,221, health factor with eigenvalue of 1,118, and social environmental factor with eigenvalue of 1,074.